Peningkatkan Keaktifan Mahasiswa Melalui Pemanfaatan Fitur Aplikasi Zoom dalam Pembelajaran Daring Mata Kuliah Pendidikan Pancasila - Aini, Nur; Murdiono, Mukhammad; Listyaningsih, Listyaningsih (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the use of the Zoom application feature in increasing student activity in Pancasila Education online learning. The study was a qualitative approach with the type of classroom action research. This study consisted of three cycles: planning, action, observation, and reflection. Researchers did observation, interviews, and documentation for collecting data. Data analysis used qualitative descriptive techniques, including data reduction, presentation, and conclusions. The study results show that the Zoom application feature in online learning in the Pancasila Education course includes material delivery, question and answer sessions and discussions, and evaluation and reflection. The Zoom application feature could increase students' ability to know, understand, and analyze, as evidenced by increased student activity scores in the first cycle of 76.43 to 82.43 in the second cycle and 83.43 in the third cycle. The increase in student activity has met the planned success index.